1980
DOI: 10.1111/j.1365-3083.1980.tb00063.x
|View full text |Cite
|
Sign up to set email alerts
|

Change in the Humoral Response of Athymic Nude Mice with Ageing

Abstract: The evolution of the serum Ig levels of Balb/c‐nu/nu mice was investigated between 1 month and 12 months of age. An increase as a function of age was observed in all classes and subclasses, which was, expressed in percentage of a nu/+ serum, from 130% to 230% for IgM, from 3% to 24% for IgG1, from 12% to 164% for IgG2a, from 28% to 62% for IgG2b, and from 10% to 50% for IgA. This increase correlates with an increase of plasma cells of each class in the bone marrow, whereas the number of plasma cells in the spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Crewther & Warner (3) reported normal serum IgG levels, but others found that the concentrations of all IgG subclasses tested are usually low (14,28). In other studies, higher levels of IgGi, IgG2a and IgG2b were reported in some individuals (12,22,25,27). In our experiments, lower total serum IgA levels were observed in nude mice but, surprisingly, serum IgG levels were markedly higher in nude mice compared to nu/-\-mice.…”
Section: S Oralissupporting
confidence: 58%
See 2 more Smart Citations
“…Crewther & Warner (3) reported normal serum IgG levels, but others found that the concentrations of all IgG subclasses tested are usually low (14,28). In other studies, higher levels of IgGi, IgG2a and IgG2b were reported in some individuals (12,22,25,27). In our experiments, lower total serum IgA levels were observed in nude mice but, surprisingly, serum IgG levels were markedly higher in nude mice compared to nu/-\-mice.…”
Section: S Oralissupporting
confidence: 58%
“…The contradictory reports on serum IgG levels in nude mice could result from exposure to different antigens and bacteria or to other factors influencing the immune system such as genetic background, age and housing conditions (22,25). Serum immunoglobulin levels in nude mice increase as a function of age (22,27). Although most studies have reported low levels of serum IgG and IgA in young (1-2 month) nude mice, others have reported that serum IgG concentration in aged (8-12 month) nude mice may occasionally reach levels higher than those in normal mice (22,27).…”
Section: S Oralismentioning
confidence: 99%
See 1 more Smart Citation
“…Nude mice have been shown to have precursors of interleukin-2-producing T cells in their bone marrow (MacDonald & Lees, 1984). The number of Thy 1-positive cells in the spleens of BALB/c nu/nu mice has been shown to increase with age (Piguet, 1980) reaching 10~o of normal values by 6 months (MacDonald et al, 1981). The number of Thy 1-positive cells in nude mice increases not only with age but also following environmental stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of aging on the downmodulation of intestinal IgA and/or IgM antibodies and IgA+ and/or IgM+ secreting cells at PP has been reported before in experimental models of aged mice ( 21 23 ). Apparent discordances among increase of IgA concentration, decrease of IgA secreting cells as well as α-chain mRNA expression reflect the aging outcome on intestinal immunity dysregulation, and they may include: i) alternative sources of IgA production like isolated lymphoid follicles as described in aged mice ( 20 , 24 ) ii) alternative routes of IgA production such as T-independent pathway (TI) in aged nu/nu mice ( 24 ). iii) a redistribution of cells among lymphoid tissues which must be mainly due to the release of stress hormones such as catecholamines and glucocorticoids which has been reported in exercised mice ( 25 ).…”
Section: Discussionmentioning
confidence: 99%